PENGARUH PERTUMBUHAN TANAMAN KAILAN (Brassica oleraceae var. alboglabra) PADA PEMBERIAN ECOENZYME YANG DIBUDIDAYAKAN SECARA HIDROPONIK - Nurul Fadilah; Resti Fevria (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Kailan is a green vegetable plant that contains lots of vitamins and minerals. Kailan plants can be cultivated hydroponically. In hydroponics, organic fertilizer application can save production costs and reduce environmental pollution. Ecoenzyme is the result of the fermentation of organic waste and sugar. Ecoenzyme can be used as a liquid organic fertilizer. In this study, using ecoenzyme organic material from orange peel and giving ecoenzyme by spraying it on plants. The purpose of this study was to determine the effect of kailan (Brassica oleraceae var. alboglabra) growth on the administration of hydroponically cultivated ecoenzymes. This research is experimental. The treatment of this study consisted of 5 treatments and 5 replications with a dilution of the ecoenzyme solution P1 (AB Mix), P2 (2 ml + 1 L water), P3 (3 ml + 1 L water), P4 (4 ml + 1 L water), and P5 (5 ml + 1 L water). The data obtained were analyzed using variance (ANOVA) with Duncan's New Multiple Range Test (DNMRT) further test. The results showed that spraying ecoenzyme affected plant height and leaf area, kailan plants were cultivated hydroponically. The highest average plant height was (P4) 16.94 cm and leaf area (P3) 6.9 cm²